India’s fiscal transition: An analytical review of the Income Tax Act, 2025, and its global alignment - Singh, Prashant; Jaiswal, Sejal; Patel, Ritesh (The International tax journal, 2026)
India’s Income-tax Act, 2025, came into effect from April 1, 2026, and represents the most comprehensive overhaul of the country’s direct tax framework since independence. This paper systematically analyses India’s new income tax statute against the direct taxation regimes of the United States Internal Revenue Code, 1986; the United Kingdom Income Tax Act, 2007; the Income Tax (Trading and Other Income) Act, 2005; and Australia’s Income Tax Assessment Acts, 1936 and 1997. The study analyses India’s taxation regime against those of these countries across dimensions, including legislative structure, tax year and residency framework, personal income tax slabs and rates, administration and e-governance, anti-avoidance mechanisms, dispute resolution systems, Tax-to-GDP ratios, and reform philosophies. Key findings reveal that, while developed nations have mature, stable, and institutionally embedded tax frameworks with high Tax-to-GDP ratios (averaging 34.1% across OECD members in 2024, compared with India's approximately 11.7%), India's 2025 Act strategically incorporates best-practice features from each comparator country. The UK's plain-language restatement experience, Australia's digital-first compliance architecture, and the USA's codified anti-avoidance framework all resonate in the design of India's 2025 Act.